2016
DOI: 10.4172/2155-9600.1000471
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Adequately Iodized Salt on Prevention of Iodine Deficiency Disorders at Household Level and Associated Factors in Lalo Assabi District, West Ethiopia

Abstract: Background: Iodine deficiency disorder is a significant public health problem in Ethiopia. Fortification of salt with iodine has been the long term and effective preventive measure against iodine deficiency disorders. However, there is no other study has been conducted on utilization of adequately iodized salt in the study area. Hence, the need to undertake this study was to provide current information regarding the utilization of adequately iodized salt at household levels in the west part of Ethiopia. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
0
11
4
Order By: Relevance
“…The iodized salt inadequacy was more severe in Combolcha residents. The finding of this study revealed that adequacy of iodized salt was much higher than reports from rural community of Maychew (33%) [21], West Ethiopia (8.7%) [22] and Gondar town, Ethiopia (28.9%) [23] and Asella Town, Ethiopia (62.9%) [24]; and similar result was observed from urban area of Sidama Zone, Ethiopia (65%) [25]. Even though there are many variation and strategies across countries, the finding of the study was also higher as compared to findings from other low income contries [13, 26].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The iodized salt inadequacy was more severe in Combolcha residents. The finding of this study revealed that adequacy of iodized salt was much higher than reports from rural community of Maychew (33%) [21], West Ethiopia (8.7%) [22] and Gondar town, Ethiopia (28.9%) [23] and Asella Town, Ethiopia (62.9%) [24]; and similar result was observed from urban area of Sidama Zone, Ethiopia (65%) [25]. Even though there are many variation and strategies across countries, the finding of the study was also higher as compared to findings from other low income contries [13, 26].…”
Section: Discussioncontrasting
confidence: 56%
“…All required data were assembled using a questionnaire organized from EDHS, UNICEF procedure protocol and from other studies [11, 20, 21] via Open Data Kit (ODK) tool. The questionnaire was compiled from validated pre-established sources and was modified contextually as per the objectives of the study [2, 10, 19–22].…”
Section: Methodsmentioning
confidence: 99%
“…4,11,14,16 In the present survey, only one in every five salt samples had adequate iodine content which is highly worrisome, as confirmed by other studies. 6,11,15,19 On the contrary, many other studies 1,8,[12][13][14]16 found more than half of the salt samples adequately iodized.…”
Section: Discussionmentioning
confidence: 93%
“…5 A study conducted by Regassa et al in western Ethiopia revealed that 70.89% families were keeping salt in in dry places and 47.4% preserving salt in closed tight containers. 18 Tamil Nadu study conducted in 2012 proved that 68.6% of families stored their salt in closed containers. 19 More than 13% households were placed the salt in sunlight exposure areas and 3.2% have habit of washing the salt before adding it in the cooking in our study.…”
Section: Discussionmentioning
confidence: 99%